Experimental infection of sheep with bovine leukemia virus (BLV): minimum dose of BLV-FLK cells and cell-free BLV and neutralization activity of natural antibodies = Infección experimental en ovinos con el virus de leucosis bovina: dosis mínima de células BLV-FLK y virus libre de células, y actividad neutralizante de anticuerpos naturales - Porta, Natalia Gabriela; Alvarez, Irene; Suarez Archilla, Guillermo Alejandro; Ruiz, Vanesa; Abdala, Alejandro Ariel; Trono, Karina Gabriela (Elsevier España, 2020)
Bovine leukemia virus (BLV) is an important cattle pathogen that causes major economic losses worldwide, especially in dairy farms. The use of animal models provides valuable insight into the pathogenesis of viral infections. Experimental infections of sheep have been conducted using blood from BLV-infected cattle, infectious BLV molecular clones or tumor-derived cells. The Fetal Lamb Kidney cell line, persistently infected with BLV (FLK-BLV), is one of the most commonly used long-term culture available for the permanent production of virus. FLK-BLV cells or the viral particles obtained from the cell-free culture supernatant could be used as a source of provirus or virus to experimentally infect sheep. In this report, we aimed to determine the minimum amount of FLK-BLV cells or cell-free supernatant containing BLV needed to produce infection in sheep. We also evaluated the amount of antibodies obtained from a naturally-infected cow required to neutralize this infection. We observed that both sheep experimentally inoculated with 5000 FLK-BLV cells became infected, as well as one of the sheep receiving 500 FLK-BLV cells. None of the animals inoculated with 50 FLK-BLV cells showed evidence of infection. The cell-free FLK-BLV supernatant proved to be infective in sheep up to a 1:1000 dilution. Specific BLV antibodies showed neutralizing activity as none of the sheep became infected. Conversely, the animals receiving a BLV-negative serum showed signs of BLV infection. These results contribute to the optimization of a sheep bioassay which could be useful to further characterize BLV infection.